Third World Studies Center Thirtieth Anniversary - Studies Center, Third World (Kasarinlan: Philippine Journal of Third World Studies; Vol 23 No 2 (2008): Culture and Politics, 2009)
Proceedings of the Third World Studies Center thirtieth anniversary held February 5, 2007, Balay Kalinaw, University of the Philippines-Diliman.
Keywords: third world